Pendampingan Pembuatan Sistem Pengukuran Tinggi Badan Otomatis Berbasis Sensor Ultrasonik di Posyandu Desa Presak Sakra - Lalu Kerta Wijaya; Fathurrahman, Imam; Hamzan Ahmadi; Muh. Kamarur Rijali Hilali; Yusril Hadi (Jurnal Teknologi Informasi untuk Masyarakat, 2025)
This community service activity aims to assist Posyandu cadres in Presak Sakra Village in developing and utilizing an automatic height measurement system based on an ultrasonic sensor. The background of this program is the predominant use of manual measuring tools, which is less efficient, prone to reading errors, and often causes long queues when many toddlers are being served. The developed system employs an HC-SR04 ultrasonic sensor, an Arduino Uno R3 microcontroller, and a 16x2 LCD to display measurement results in real time, making the device more practical and easier to operate for Posyandu cadres. The implementation method includes hardware and software design, laboratory testing of the device, implementation at the Posyandu, training for cadres, and evaluation of system effectiveness in routine health services. Test results indicate that the device can measure body height with a deviation of 0 to 1 cm from the actual height, which is still acceptable for basic health services. In addition to improving efficiency and accuracy, this activity strengthens the role of higher education institutions in transferring appropriate technology and is expected to be replicated in other Posyandu to support improved quality of community health services.